Construction of the Hill48 and Yld89 for Auto-body Steel Sheets considering the Strain Rate - Bae, G. H.; Huh, H.; Kim, S. B.; Lee, C. S.; Lou, Y. (Institut für Umformtechnik - Technische Universität Dortmund, 2010)
This paper deals with the anisotropic material properties and the initial yield locus considering the strain rate. Uni-axial tensile tests are performed with variation of the strain rate in order to obtain flow stress curves and the tensile properties. The R-values have been measured with a high speed camera by analyzing the deformation history during the tensile test. Anisotropy of auto-body steel sheets have been described by using Hill48 and Yld89 (Barlat89) yield functions according to the strain rate ranged from 0.001/sec to 100/sec. Hill48 and Yld89 yield loci of auto-body steel sheets at various strain rates have been constructed in order to visualize the initial yield state. The performance of two yield criteria is evaluated by comparing yield loci constructed in the principal stress plane. The initial yield locus becomes different from the static one when the strain rate is considered to describe the anisotropy of the steel sheets.
Keywords: anisotropy; auto-body steel sheets; sheet metal forming; strain rate; yield function; 620; 670